Very early remission and increased apoptosis with the use of Pentoxifylline in children with acute lymphoblastic leukemia - Salceda-Rivera, Violeta; Ortiz-Lazareno, Pablo C.; Hernández-Flores, Georgina; Vazquez-Urrutia, Jorge R.; Meza-Arroyo, Jesus; Pardo-Zepeda, Monzerrat; Romo-Rubio, Hugo; Barba-Barba, Cesar; Sánchez-Zubieta, Fernando; Barrón-Gallardo, Carlos Alfredo; Gonzalez-Ramella, Oscar; Bravo-Cuellar, Alejandro (Frontiers in Oncology, 2024)
IntroductionDespite the improvement in survival in acute lymphoblastic leukemia (ALL), there are still cases with evasion of chemotherapy-induced apoptosis. The IKK/NF-κB signaling pathway contributes to antiapoptotic gene expression. Pentoxifylline (PTX) inhibits IkB phosphorylation, blocking NF-κB and antiapoptotic activity. MethodsWe conducted a randomized, double-blind clinical trial on pediatric ALL patients undergoing induction therapy, assigning them to PTX or placebo group. Bone marrow aspirates were obtained on days 1, 8, 15, and 22. Apoptosis was assessed using Annexin-V/propidium iodide. ResultsResults indicated that the PTX group exhibited higher apoptosis on day-8 (41.3% vs. 19.4%, p =0.029) and day-15 (35.0% vs. 14.2%, p <0.01). On day-8, the PTX group displayed an MRD of 0.25% vs. 18.2% (p <0.01) in placebo group; on day-15, the PTX group demonstrated an MRD of 0.09% vs. 1.4% (p =0.02). Patients achieving an MRD <0.01% on day-8 demonstrated a 3-year Overall Survival (OS) of 81.6% vs. 58.3% (p =0.03); on day-15, patients with MRD <0.01% had a 3-year OS of 77.9% vs. 54.5% (p =0.03). The PTX group achieved an MRD of <0.01% earlier on days-8 and 15, along with a higher apoptosis rate, indicating a more favorable therapeutic response. In the entire cohort, patients achieving MRD <0.01% on day-8 or 15 displayed superior OS. ConclusionOur study demonstrates that PTX enhances apoptosis and reduces MRD in pediatric acute lymphoblastic leukemia patients.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT02451774.